Assessing wagon pack sizes in longitudinal train dynamics simulations. Issue 3 (1st September 2020) - Wu, Qing; Cole, Colin; Spiryagin, Maksym
ABSTRACT: Wagon packs replace some couplers with draw-bars to reduce slacks in the train. Prior to the decision of wagon pack sizes, the implications of wagon pack sizes for train dynamics and connection system fatigue life have to be assessed. This paper uses longitudinal train dynamics (LTD) simulations to assess three different wagon pack sizes (1-pack, 2-pack and 4-pack) for a real-world heavy haul train configuration on a real-world railway. Simulations are conducted to assess the implications of wagon pack sizes during train starting, speed correction braking, emergency braking and whole-trip train operations. In-train forces and train speed differences are compared and analysed for all simulations. Wagon connection fatigue life is compared for the whole-trip train simulations. The results show that both 2-pack and 4-pack plans can decrease the in-train force magnitudes during train operations. However, the improvements from the 1-pack plan to 2-pack plan are evidently larger than those when moving from the 2-pack plan to 4-pack plan. The results also show that force magnitudes are not the major conflict for the studied cases. Fatigue life calculations show that the 2-pack plan and 4-pack plan can increase the wagon connection system fatigue life by 69% and 176%, respectively Table 2 .